Material culture as a method of urban design research: modern challenges - Y. O. Butsykina, (Ukrainian Cultural Studies, 2021)
Article discusses material culture as one of the thorough ways to determine the methodological basis for the cultural study of design, design practices and, including urban design in the world and in Ukraine. The article turns to the researchers who initiated the actual exploration of material culture outside of archeology and cultural anthropology, which will eventually lead us to modern views on material culture as a relevant approach in culturological analysis of the design of objects, objects of urban space – in particular.The article provides the actualization of this issue in the application to the culturological study of urban design itself, taking into account its specifics. It outlines some compelling arguments as to why the discourse of material culture is becoming increasingly relevant in the study of urban design and culturological research in particular. A number of approaches is shown within which this combination becomes relevant. Especially given the design of Ukrainian cities and its cultural research, where the need to overcome the dichotomy of spiritual and material culture has long been ripe.
Keywords: artifact, material culture, objectification, urban design, value